METHODOLOGY TO DEVELOP CRITICAL THINKING THROUGH SOCIAL NETWORKS (Proceedings of the International Conference on Education, 2021)
In the age of information and data analysis, students do not always have the disciplinary and / or transversal competences, nor do they always have the correctstrategies to select content and arguments that reinforce the construction of their disciplinary criteria, even though the tools to achieve it are at their fingertips. In the new educational model of the Tecnológico de Monterrey, a priority is to contribute to higher education through the development of critical thinking based on the personal motivations of students. As a link between the knowledge acquired and their context, an alternative that allows the above is to promote the dissemination of collective knowledge in social networks (SN). In the present work, an educational innovation is proposed that allows to combine the knowledge acquired in the classroom with the use of SN, in order to develop critical thinking in students. The methodology includes 3 phases: i) Students develop content related to the course topics, ii) Students share this content on social networks, iii) Teachers monitor the impact of publications and do the sentiment analysis. This process was successfully implemented to a total of 150 undergraduate students of different specializations and semesters during four academic terms in different subjects of the four Professional Level schools. Pre and post tests, where critical thinking competence criterion were evaluated, were performed, resulting in 74% of the students improving in at least one criteria Additionally, it was observed, based on entry and exit surveys, that the appropriate and guided use of the different SN’s, positively modifies the student's perception of the content of the subjects and the teaching of the class, since it allows them to relate academic topics with social reality, thus forming their own and responsible criterion on the published content.
Keywords: Social Networks; Critical Thinking; Educational Innovation; Higher Education; Sentiment analysis